Examining the Effects of E-Satisfaction, E-Trust and Perceived Value on Repurchase Intention among Young Adults - Muhammad, Nur Shahrulliza; Mansor, Aida Azlina; Rohisham, Iman Haiqal; Afendy, Irfan Hadeef Taufik; Ismadi, Muhamad Zahir; Mohd Azli, Alia Amrina; Zakaria, Aina Nadhirah; Azmi, Nurul Ain (Information Management and Business Review, 2024)
This study adapted some of the dimensions in the ES-QUAL model that contribute to e-satisfaction, with additional factors of e-trust and perceived value about repurchase intention among young adults in an online shopping setting. The research methodology involved a sample size of 103 full-time students of Bachelor of Business Administration (BBA) Retail Management (Hons.) in UiTM Puncak Alam aged between 18 to 26 years old, utilizing a structured adapted questionnaire to capture demographic profiles and components of e-satisfaction, e-trust and perceived value about repurchase intention. The descriptive statistics show a substantial increase, with the highest mean obtained by e-satisfaction, followed by perceived value and e-trust. In addition, the finding implies that there is a high degree of repurchase intention among these students.